Decline in ventricular function as a result of general anesthesia in pediatric heart transplant recipients. (30th October 2016) - Elhoff, Justin J.; Chowdhury, Shahryar M.; Taylor, Carolyn L.; Hassid, Marc; Savage, Andrew J.; Atz, Andrew M.; Butts, Ryan J.
Abstract: Echocardiography is frequently performed under anesthesia during procedures such as cardiac catheterization with EMB in pediatric HTx recipients. Anesthetic agents may depress ventricular function, resulting in concern for rejection. The aim of this study was to compare ventricular function as measured by echocardiography before and during GA in 17 pediatric HTx recipients. Nearly all markers of ventricular systolic function were significantly decreased under GA, including EF (−4.2% ±1.2, P  < .01) and RV FAC (−0.05 ± 0.02, P  = .04). Subjects in the first post‐transplant year (n = 9) trended toward a more significant decrease in EF vs those beyond the first post‐transplant year (n = 8; −6.0% ±1.2 vs −2.1 ± 2.0, P  = .1). This information quantifies a decline in biventricular function that should be expected in pediatric HTx recipients while under GA and can assist the transplant clinician in avoiding unnecessary treatment of transient GA‐induced ventricular dysfunction.